2006
DOI: 10.1021/jp063689o
|View full text |Cite
|
Sign up to set email alerts
|

Optical and X-ray Emission Spectroscopy of High-Power Laser-Induced Dielectric Breakdown in Molecular Gases and Their Mixtures

Abstract: Large-scale plasma was created in molecular gases (CO, CO2, N2, H2O) and their mixtures by high-power laser-induced dielectric breakdown (LIDB). Compositions of the mixtures used are those suggested for the early earth's atmosphere of neutral and/or mildly reducing character. Time-integrated optical spectra emitted from the laser spark have been measured and analyzed. The spectra of the plasma generated in the CO-containing mixtures are dominated by emission of both C2 and CN radicals. A vibrational temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
1
31
0
1
Order By: Relevance
“…The same behavior was observed starting with HCONH 2 as a single molecular source of C, H, O & N. Figure 1 shows typical emission spectra of laser induced breakdown shock wave plasma in such simple atmospheres of C, H, O & N bearing molecules. Typical vibrational temperatures of molecular species range 12,3335 between 4200–6500 K while excitation temperature of atoms does not exceed 9300 K 33 . This figure is compiled from several measurements published in our previous papers so as to show typical, representative spectra 12,33,34,36 .
Figure 1Compiled emission spectrum of laser induced breakdown in mixture of C, H, O & N bearing molecules 12,33,34,58 .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same behavior was observed starting with HCONH 2 as a single molecular source of C, H, O & N. Figure 1 shows typical emission spectra of laser induced breakdown shock wave plasma in such simple atmospheres of C, H, O & N bearing molecules. Typical vibrational temperatures of molecular species range 12,3335 between 4200–6500 K while excitation temperature of atoms does not exceed 9300 K 33 . This figure is compiled from several measurements published in our previous papers so as to show typical, representative spectra 12,33,34,36 .
Figure 1Compiled emission spectrum of laser induced breakdown in mixture of C, H, O & N bearing molecules 12,33,34,58 .
…”
Section: Resultsmentioning
confidence: 99%
“…Compiled emission spectrum of laser induced breakdown in mixture of C, H, O & N bearing molecules 12,33,34,58 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, spectroscopic measurements performed on the dc electric glow in N 2 spectrum showed that although numerous molecular bands appear, nitrogen atomic lines are not present. Besides, the second positive system of N 2 and the first negative system of N (7,5) of N 2 (C-B). The upper panel of figure 7(a) shows the LIDB emission spectrum of nitrogen in the spectral region 2925-3175Å of nitrogen.…”
Section: Identification Of the Chemical Species In The Laser-induced mentioning
confidence: 99%
“…The LIDB nitrogen spectrum recorded by Babankova and co-workers [7] in the spectral region 300-700 nm is composed of one broadband formed from unresolved lines of N + and from the v = 0 − v = 0 electronic transition of N + 2 (B 2 + u -X 2 + g band system). The LIDB spectra from N 2 reported by Nordstrom [8] and Hanafi et al [9] are composed of N and N + atomic lines without identification of any molecular emission.…”
Section: Introductionmentioning
confidence: 99%
“…Such a period does not take place in the gas puff because the LIDB plasma expands through the thin layer of helium directly into vacuum. Experiments with the gas puff also provide the unique opportunity to look through the vacuum and observe the short-wavelength emission of LIDB plasma (Babankova et al 2006b, Figure 2). This cannot be done in the static cell due to strong absorption of short-wavelength radiation in the cold, dense gas.…”
mentioning
confidence: 99%